PERSEPSI DAN EKSPEKTASI ANGGOTA KOPERASI TANI PERKASA TERHADAP KONFLIK DENGAN PT. CITRA RIAU SARANA DI DESA PASAR BARU KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Novendra Novendra; Rosnita Rosnita; Kausar Kausar (Indonesian Journal of Agricultural Economics, 2016)
Conflict is a problem that arises and unavoidable of human life. Conflict occurs because of differences of opinion, different purposes, or poor communication, causing the appearance of a conflict. The purpose of this study to determine the perceptions and expectations of members of Tani Perkasa Cooperative and PT. Riau Sarana Citra to understanding the conflict in Pasar Baru Village District of Pangean. This study used a survey method. To determine the respondents used key informants and samples. The sampling method is purposive sampling. Respondents were drawn as many as 70 members of the Tani Perkasa Cooperative as a sample. In this study using 5 key informant. The data have been obtained in the field were analyzed by descriptive qualitative, then make the tabulation of the distribution of respondents from each of the variables studied. To describe the perception variables Tani Perkasa Cooperative members to use 5W + 1H conflict. While to analyze the expectations of members of Koperasi Tani Perkasa to the conflict used the Likert Scale. The results showed that: (1) Perception of Tani Perkasa Cooperative to understand the conflict in the category measured from the perception of understanding of the problem of conflict, perceptions of understanding of the purposes of conflict actors, and perceptions of understanding the conflict actors. (2) Expectations Tani Perkasa Cooperative to the conflict was in the category of high expectations with a score of 3.58 as measured from goal, pathway thinking, and agency thinking.